SOURCES OF RESEARCH ON ETHNOPOLITICS OF UKRAINIAN AUTHORITIES DURING THE NATIONAL LIBERATION STRUGGLES OF 1917–1921 - Лазарович, М. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The sources of the ethnonational policy of Ukrainian government under the conditions of the liberation struggles of 1917–1921 years are explored. Materials from the funds of central and local archives are analyzed. A comparative survey of historiographical literature, scientific reference and encyclopedic publications, statistical collections, periodicals was carried out.